Faculty’s and students’ perceptions on the oral skills necessary for success in medical studies and oral proficiency problems faced by medical students - Abdul Malik, Faridah; Othman, Khairiah (2019)
Due to the importance of being able to communicate well in English for their studies and future career, this study attempted to compare and contrast between the perceptions of medical students and faculty members on the oral skills that are necessary for success in medical school and the extent of oral proficiency problems faced by the students. To this end, two sets of questionnaire were distributed to 50 faculty members and 256 medical students who were in their clinical years. The results show that there is concordance of opinion by both the medical students and faculty members on the oral English problems as faced by the students. However, it was clear that several of the oral tasks perceived as integral to their success as medical students were not judged with the same gravity as the faculty members. This was an unexpected finding and perhaps it is something worth exploring further. The implications are that the real-life experiences of the faculty members do not correspond to the perceived expectations of the medical students. This is subject to further studies in the future.